Cobalt and Nickel Complexes Bearing 2, 6-Bis(imino)phenoxy Ligands:Synthesis and Ethylene Oligomerization Study. Issue 4 (2006) - Du, Jian-Long; Li, Li-Jun
Abstract : A series of new cobalt and nickel complexes MLX2 (M = Co or Ni, X = Cl) bearing 2, 6-bis(imino)phenoxy ligands have been synthesized. Treatment of the complexes with methylaluminoxane (MAO) leads to active catalysts for ethylene oligomerization. The oligomers are olefins from C4 to C6 .